Further Correction: Hypoxia inducible factor (HIF) as a model for studying inhibition of protein–protein interactions. Issue 7 (1st February 2018) - Burslem, George M.; Kyle, Hannah F.; Nelson, Adam; Edwards, Thomas A.; Wilson, Andrew J.
Abstract : Correction for 'Hypoxia inducible factor (HIF) as a model for studying inhibition of protein–protein interactions' by George M. Burslem et al., Chem. Sci., 2017, 8, 4188–4202.